Factors that influences the adoption of Takaful product in Selangor: a case study in Selangor / Wan Afiqah Wan Seman - Wan Seman, Wan Afiqah (Faculty of Business and Management, 2018)
The aim of this research is to investigate the factors that influence the adoption of Takaful product (Islamic Insurance) in Selangor. As for this research, causal research will be used to analyse cause and effect relationship among factors that may affect adoption of Takaful product in Selangor and a cross sectional survey methods using a survey questionnaire is used. The dependent variable used in this research is Adoption of Takaful Product. While the independent variables are Compatibility, Social influences, Awareness of Shariah Compliance, Knowledge and Perception. The research is an empirical investigation based on surveys completed 100 respondents in Selangor. The data will be analysed through IBM SPSS Statistics VV22.0. The results are interpreted using these methods which are descriptive statistics, KMO test, reliability and validity tests, correlation and regression analysis. This research revealed that there are significant relationship between compatibility, social influence and knowledge towards adoption of Takaful product. However, this research did not find significant relationship between awareness of Shariah compliance and perception towards adoption of Takaful product. This research is very beneficial for those who work in Insurance industry, especially in market where Muslims are dominant to improve and develop of Takaful industry to be better than before.